Comparative analysis of microbial contamination in diesel fuels using MALDI-TOF MS - Agnieszka Ludwiczak; Tomasz Zieliński; Ewelina Sibińska; Grażyna Czeszewska-Rosiak; Michał Złoch; Joanna Rudnicka; Andrzej Tretyn; Paweł Pomastowski (Scientific Reports)
Abstract Microbiological contamination in fuels poses a significant threat to fuel quality, operational safety, and the efficiency of fuel systems. Effective management of microbial risks can extend fuel systems’ lifespan and minimize the environmental footprint of fuel usage. Therefore, we aimed to identify the microbiological contaminants using two MALDI-TOF MS systems (Bruker Daltonik GmbH and Zybio Inc.). Detection and characterization of microbiological contamination in fuels were performed with further validation by 16 S rRNA gene sequencing. Microorganisms collected from three types of diesel fuel were cultured, and fuel samples were analyzed. Significant differences in microbiological contamination were observed between the fuel types, with 272 isolates of bacteria and fungi identified across all fuel samples. Ekodiesel Ultra B0 had the highest number of identified microorganisms. The Zybio system identified 48% of all microorganisms at the species level, whereas the Bruker system identified only 33%. The 16 S rDNA sequencing confirmed proteomic identifications by the MALDI systems with high accuracy. Our study indicates that MALDI-TOF MS technology can effectively assess microbiological contamination in fuels. Integrating MALDI-TOF MS with other molecular techniques could provide a comprehensive view of fuel’s microbial communities.